Konstelasi Pemenuhan Hak Warga Negara Oleh Masyarakat Penghayat Kepercayaan Parmalim - Valerie Amalinda (HK-Publishing, 2022)
According to Marshal, there are three segments of citizens rights, namely civil rights, social rights, and political rights. Representation of social rights is interpreted as to embrace a religion that they believe is part of the realization of Human Rights (HAM). However, in practice there is still a lot of discrimination that occurs against adherents of this belief, not infrequently the community's stigma about this belief system is heretical and deviant teachings, worshiping idols and allying with Satan. Parmalim is one of the local beliefs and religions typical of the Batak tribe which also often gets discriminatory treatment from the community. Even the fulfillment of the rights of citizens which should be absolutely granted, cannot be given because it is collided with their status as believers. With qualitative methods and data collection techniques in the form of literature studies, the researcher wants to see how the Parmalim community gets discriminatory treatment to fight for their rights as citizens, and it is known that discriminatory treatment is still obtained even though it has been regulated by the Constitutional Court Regulation which regulates this.Keywords: Citizens Rights, Religion, and Parmalim